The Effect of Work Discipline, Position Mutation and Work Environment on Employee Performance at the Secretariat Padang Pariaman Regency - Aggraini, Meri; Martha, Lidya (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the effect of work discipline, position transfer and work environment on employee performance at the Regional Secretariat of Padang Pariaman Regency. The sample in this study amounted to 146 employees or respondents. Research data were collected from respondents' results and analyzed by multiple linear regression and hypothesis testing. The results of this study indicate that work discipline has a positive effect and job transfer has a positive effect and the work environment has a positive and significant effect on employee performance. It can be seen that the significant value of work discipline, job transfer and work environment on employee performance is a value of 0.000 <0.05 and a t-count of 4.999 from a t-table of 1.97681